Migration and Agrarian Change in Eastern Hill Region of Nepal - Timsina, Tirtha Raj (Swarnadwar, 2024)
Migration is a fundamental factor of human mobility and civilization through which people largely shift their ways of living to secure better life. The agrarian mode of social stratification dates back to the human civilization that have also been changing across. Among the various sectors, agriculture is considered to be the backbone of developing economy which has been largely influenced by mobility of the people. By considering this fact, the true value of migration lies on the rapid transformation of existing agrarian pattern of most of the economy. The aim of this paper is to analyze the role of migration in agrarian social change in the eastern hill of Nepal. This research paper is primarily based on the secondary data obtained through reviewing different published as well as digital scholarly sources and other official records to obtain the required information. The study reveals that migration is one of the dominant factors of agrarian social change in hill regions of Nepal. Since, agriculture growth is inevitable for better rural livelihood, the gradual diversification of rural livelihood dominantly influenced the agrarian social structure and the development of rural hill regions.